The Effects of High Performance Work Practices on Job Satisfaction in the United States Steel Industry - Berg, Peter (Relations industrielles / Industrial Relations, 1999)
A unique data set is used to examine how different practices associated with high performance work systems in the steel industry affect the job satisfaction of workers. While the effect of these practices on organizational performance is widely studied, few have examined their effects on workers. Their analysis in this paper is based on data from a sample of 1,355 hourly workers in the US steel industry across 13 plants. The results indicate that the effect of high performance practices on job satisfaction depends primarily on how work roles and job duties are defined, on good employee-management relations and on practices that help balance work and family responsibilities. These results show that those who are able to use their skills and knowledge on the job, those who report positive employee-management relations, and those who believe the company helps them balance work and family responsibilities have relatively high probabilities of being very satisfied with their jobs.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Job satisfaction; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Steel industry; Studies; Work environment

Dignity at Work for Low Wage, Low Skill Service Workers - Berg, Peter; Frost, Ann C. (Relations industrielles / Industrial Relations, 2005)
Using responses from a telephone survey of 589 low wage, low skill workers in US hospitals, the authors investigate the workplace features that influence workers' perceptions of dignity at work. Both work organization variables and union representation are investigated as potential factors affecting workers' perceptions of fair treatment by their employer, intrinsically satisfying work, and economic security. Work organization and union representation have little effect on dignity at work with the exception of their association with higher wages and therefore a greater degree of economic security. Results indicate that higher pay, adequate levels of staffing and resources, and access to training are the variables that are most closely associated with dignity on the job.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Dignity; Labor Unions; Perceptions; Polls & surveys; Skills; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Variables; Wages & salaries

Working-Time Configurations: A Framework for Analyzing Diversity Across Countries - Berg, Peter; Bosch, Gerhard; Charest, Jean (ILR Review, 2014)
Working-time practices across the developed world have exploded with diversity during the past few decades. The once standard 8-hour day and 40-hour workweek that emerged and reigned throughout much of the 20th century have given way to an increasing variety of working-time arrangements. Flexible schedules, in which hours can vary daily or weekly, and nonstandard work arrangements, such as fixed term, on-call, temporary, or part-time, are widely used at the workplace. In addition, we have witnessed the growth of zero-hour contracts that make no guarantee to provide workers with weekly working hours or a reliable income, while requiring employees to work on very short notice with very unpredictable schedules; annualized hours contracts that allow for work hours to vary over a year; and working-time accounts that allow employees to bank hours worked over a set weekly standard and to then draw on these accounts for paid time off.